2025 mating list for catla genetic improvement program - Hamilton, Matthew (WorldFish, 2025)
This is a mating list for catla families targeted for production in 2025 as part of the WorldFish Carp Genetic Improvement Program. It was developed based on genetic analysis to generate EBVs, optimal selection to identify parental family contributions, spawning readiness of candidate individuals, past contributions from previous spawn batched and mate allocation to minimise inbreeding (adopting assortative mating).